Clinicopathological and prognostic role of MMP-9 in esophageal squamous cell carcinoma: a meta-analysis - Zeng, Rong; Duan, Lei; Kong, Yuke; Liang, Yaojun; Wu, Xiaolu; Wei, Xuequan; Yang, Kehu (Chinese Journal of Cancer Research; Vol 25, No 6 (December 26, 2013): Chinese Journal of Cancer Research, 2013)
Objective: Many studies reported that matrix metalloproteinase-9 (MMP-9) participated in the development of esophageal squamous cell carcinoma (ESCC) and resulted in poor prognosis, however, they all included few patients and had inconsistent results. So we conducted a meta-analysis to explore the correlation between overexpression of MMP-9 and the clinicopathological characteristics and overall survival (OS) of ESCC. Methods: PubMed, EMBASE, Web of Science, Chinese Biomedical Literature Database, Google Scholar and other databases were searched for relevant studies. The Newcastle-Ottawa quality assessment scale was used to assess the methodological quality of included study and RevMan 5.2 software was used to conduct meta-analysis. Results: A total of 35 studies were included, and the results of meta-analysis showed that overexpression of MMP-9 was associated with grade of differentiation [well/moderate vs. poor: odds ratio (OR): 0.39, 95% confidence interval (CI): 0.29-0.52; P